2016
DOI: 10.1038/ncomms10290
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies variation at 6q25.1 associated with survival in multiple myeloma

Abstract: Survival following a diagnosis of multiple myeloma (MM) varies between patients and some of these differences may be a consequence of inherited genetic variation. In this study, to identify genetic markers associated with MM overall survival (MM-OS), we conduct a meta-analysis of four patient series of European ancestry, totalling 3,256 patients with 1,200 MM-associated deaths. Each series is genotyped for ∼600,000 single nucleotide polymorphisms across the genome; genotypes for six million common variants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Clinical trial information on these patients has been previously reported 47 48 49 50 . The primary analysis end point was myeloma-specific overall survival and analysis was performed as previously described 51 . Cox regression analysis was used to derive genotype-specific hazard ratio and associated 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trial information on these patients has been previously reported 47 48 49 50 . The primary analysis end point was myeloma-specific overall survival and analysis was performed as previously described 51 . Cox regression analysis was used to derive genotype-specific hazard ratio and associated 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the clinical relevance of most mutations has not yet been determined and is undergoing investigation in large sequencing programs (CoMMpass, The Myeloma Genome Project and others). 39 , 40 No mutation screening has yet been implemented in standard clinical workflows, but mutational analyses may help to identify potential therapeutic targets (such as BRAF mutations) and to stratify of patients in clinical trials.…”
Section: European Myeloma Network Recommendationsmentioning
confidence: 99%
“…P53, RB1, DIS3, CDKN2A and CDKN2C [193] , and mutations in members of the NF-κB pathway [194] and STAT3 [195] . The constitutional genotype of the tumor also plays a role in determining patient outcome [196] . Mutations in CDKN2A, a stabilizer of p53 increase sensitivity to chemotherapy [197] .…”
Section: Role Of Genetics and Genomics For Drug Resistancementioning
confidence: 99%